MicroRNA Regulation in the Inflammatory Response - Martin, Athena (2023)
The interplay between poly(A) tail length and miRNA regulation has been previously studied. Moretti et al., (2012) found that longer poly(A) tail lengths correlated with greater miRNA mediated repression, with miRISC association triggering the displacement of PABP from the poly(A) tail. This is in agreement with Rissland et al., (2017) who found that miRISC has the ability to alter the composition of the mRNP, in particular the association of PABP and eIF4G while not impacting on poly(A) tail length. On the other hand, Eisen et al., (2020), found that miRNAs only stimulated deadenylation of transcripts with very short poly(A) tails.